Isolation of Cellulosic Material from Outer Skin of Drumstick and Jarul Fruit and Their Derivatization - Tasnim, Tahsina; Akter, Khadiza; Rahman, SM Mizanur; Rahman, M Azizur (Dhaka University Journal of Science, 2016)
Abstract not available Dhaka Univ. J. Sci. 64(2): 177-178, 2016 (July)